Where's the Educational Virtue in Flourishing?. Issue 3 (8th September 2021) - Carr, David
Abstract: Recent philosophy and theory of education have witnessed considerable attention to the notion of flourishing as a benchmark or guiding principle for educational practice. There can also be little doubt that — while not all recent advocates of flourishing have drawn explicitly on Aristotle — a focus on flourishing has emerged in the wake of latter‐day neo‐Aristotelian virtue ethics, and contemporary virtue ethicists have indeed been leading educational advocates of flourishing. However, while focusing more on basic formal features of the concept than on the detail of recent educational accounts, David Carr's main aim in this essay is to show that the notion of flourishing — along with ideas of moral and other virtue and (personal or literary) exemplification with which it has lately been associated — ultimately falls well short of illuminating any significant educational issues or concerns.